A large-scale purification of recombinant histone H1. 5 from Escherichia coli - Pyo, Sang-Hyun; Lee, Jae-Hyun; Park, Heung-Bok; Hong, Seung-Suh; Kim, Jin-Hyun (Protein Expression and Purification, 2001)
An Escherichia coli expression system has been constructed for production of biologically active recombinant histone H1.5. A process of fermentation and purification method at a large scale has been developed. Recombinant histone H1.5 was released from the high density cultured cells by high-pressure homogenization. For an efficient removal of cell debris and partial purification of basic histone H1.5 in a single step, the whole cell lysates were directly loaded onto an expanded bed column packed with the strong cation exchanger (Streamline SP). Complete removal of various impurities was achieved by a combination of hydroxyapatite chromatography and the following cation exchange chromatography with high grade strong cation exchanger (POROS 20 HS), and finally endotoxins were removed by ultrafiltration using a 100-kDa cut-off membrane, which gave the level of endotoxin below 0.5 EU/mg. The …